Board Characteristic and Financial Restatement - Putri, Ni Ketut Wahyu; Rustiarini, Ni Wayan; Dewi, Ni Putu Shinta (University of Merdeka Malang, 2021)
This study explores the role of board characteristics, namely the Board of Directors (BoD) and the Board of Commissioners (BoC), on the possibility of financial restatement. BoD characteristics were analyzed based on BoD size, female, and overconfidence. Meanwhile, BoC characteristics were analyzed based on BoC size and independent BoC. The population is all manufacturing companies on the Indonesia Stock Exchange for the 2017- 2019 period. Determination of the sample using the purposive sampling method. The number of samples used is 32 manufacturing companies or 96 observational data. This study using logistic regression to hypotheses testing. The results showed that two variables, namely female of BoD and independent of BoC, reduced the possibility of financial restatement. However, three other variables, including BoD overconfidence, BoD size, and BoC size, do not affect the possibility of financial restatement.DOI: 10.26905/jkdp.v25i3.5883